PEMANFAATAN MODEL DIGITAL STORYTELLING (DST) SEBAGAI INOVASI PEMBELAJARAN MAHARAH KALAM PADA PEMBELAJAR BAHASA ARAB GENERASI Z - Isniyatun Niswah MZ; Nurul Hanani; Lailatul Qomariyah; Nurul Hidayah
Language is the door to knowing other sciences, and these language skills will not be achieved through repetitive education without paying attention to the needs of students in learning. Today's students are students who are called millennials and generation Z, where they live in the age of digital technology. Of the many proficiencies that must be achieved in learning Arabic, this is a scourge for students who have a non-Pakistani background. They feel that learning Arabic is quite complicated and difficult. Not only that, the difficulties that occur are also caused by traditional learning models and tend to be monotonous. Therefore, the presence of technology is expected to provide solutions in learning Arabic that are fun and innovative. One of the technology models that can be applied Digital Story Telling is a practice that combines personal stories with multimedia in the form of images, audio and text. From the description above, the researcher focuses on how the implementation of the Digital Story Telling (DST) model in learning maharah kalam for students majoring in Arabic Language Education at Hasyim Asy'ari University. The method in this research is descriptive qualitative research with data collection techniques in the form of observation, interviews, and documentation. As well as data analysis techniques with data reduction, data presentation and drawing conclusions.